A Retrospective Review of Patients Managed with the Pneux PY™ VAP Prevention System. (April 2014) - Smith, Neil; Khan, Faheem; Gratrix, Andrew
Ventilator-associated pneumonia (VAP) is commonplace in intensive care and has implications for patients' morbidity and mortality in hospital. A range of interventions exists to prevent the development of VAP. We reviewed the impact of the PneuX PY™ VAP prevention system on the incidence of VAP and its effects on local practice. In total, 48 patients in a mixed medical and surgical intensive care unit received the PneuX PY VAP prevention system and its associated care package in 2010. The VAP rate for this cohort of patients was found to be 6.25% (n=3) in the local context of historical VAP rates above 26%. Notably, 17% of extubations were unplanned, of which almost two-thirds were self-extubations. The PneuX PY VAP prevention system facilitated lower VAP rates than those documented elsewhere and highlighted the incidence of unplanned extubations in local practice. Further evaluation of the implementation of the PneuX PY VAP prevention system in intensive care areas, in tandem with large-scale evaluation of its effectiveness, are still required.